Let P n = n 1 + 3 n 3 1 + 5 n 5 1 + 7 n 7 1 + ⋯ .
If the value of n = 2 ∑ 9 9 2 P n is equal to ln α , find α .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Ya... Exactly the intended solution...Nice (+1)... Just a typo in second last line!
Write given series as integral from 0 to 1/n of (1+x^2 + x^4............)dx
Use formula of infinite Geometric progression as x<1 and then integrate to get the sum as 1/2 [ ln(n+1)-ln(n-1) ]
Then to evaluate final answer use telescoping product
I integrated -(1/n^2 + 1/n^4 + 1/n^6 +...) and took the constant of integration as zero due to cognitive bias, so that I can arrive at the mentioned expression. Do I need to worry about the constant of integration here?
Yep, you have to.
Integrate it with upper bound say, k and lower bound 0
python code:
import cmath as m
def fun(x):
return ((m.log(1+(1/x)))-(m.log(1-(1/x))))/2
sum=0
for i in range(2,100):
sum=sum+2*fun(i)
print(str(m.exp(sum.real)))
Problem Loading...
Note Loading...
Set Loading...
By Maclaurin series , we have:
ln ( 1 − x 1 + x ) 2 1 ln ( 1 − x 1 + x ) ⟹ n = 2 ∑ 9 9 2 P n = 2 x + 3 2 x 3 + 5 2 x 5 + 7 2 x 7 + . . . = x + 3 x 3 + 5 x 5 + 7 x 7 + . . . = n = 2 ∑ 9 9 ln ( 1 − n 1 1 + n 1 ) = n = 2 ∑ 9 9 ln ( n − 1 n + 1 ) = n = 2 ∑ 9 9 ( ln ( n + 1 ) − ln ( n − 1 ) ) = n = 3 ∑ 1 0 0 ln n − n = 1 ∑ 9 8 ln n = ln 9 9 + ln 1 0 0 − ln 1 − ln 2 = ln ( 2 9 9 0 0 ) = ln 4 9 5 0
⟹ α = 4 9 5 0